FLOUTING MAXIM OF RELEVANCE IN HOTEL TRANSYLVANIA: TRANSFORMANIA MOVIE - Dewi, Ni Kadek Kurnia Nareswari (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
This research focuses on finding the flouting maxim of relevance in characters’ conversations in Hotel Transylvania: Transformania movie. This study aims to find out the flouting maxim of relevance uttered by the characters in Hotel Transylvania: Transformania movie and to identify the reasons for the characters flouting the maxim of relevance. The method that used in analyze the data is the descriptive qualitative method. The theory proposed by Grice (1975) about cooperative principle was applied to identify the flouting maxim of relevance in this movie. Furthermore, the theory from Christoffersen (2005) was applied to classify the possible reasons for the characters flouting the maxim of relevance in their conversation. Results that from this study show two out of eight reasons for the characters flouting the maxim of relevance in their conversation along the movie. The reasons are to hide the truth and convince the hearer. Hiding the truth was often used by the characters in this movie. The main character, Drac, was a character that often flouted the maxim of relevance.